Continued Selenium Biofortification of Carrots and Broccoli Grown in Soils Once Amended with Se-enriched S. pinnata - Bañuelos, Gary S.; Arroyo, Irvin S.; Dangi, Sadikshya R.; Zambrano, Maria C. (Frontiers in Plant Science, 2016)
Selenium (Se) biofortification has been practiced in Se-deficient regions throughout the world primarily by adding inorganic sources of Se to the soil. Considering the use of adding organic sources of Se could be useful as an alternative Se amendment for the production of Se-biofortified food crops. In this multi-year micro-plot study, we investigate growing carrots and broccoli in soils that had been previously amended with Se-enriched Stanleya pinnata Pursh (Britton) three and four years prior to planting one and two, respectively. Results showed that total and extractable Se concentrations in soils (0-30 cm) were 1.65 mg kg-1 and 88 µg L-1, and 0.92 mg kg-1 and 48.6 µg L-1 at the beginning of the growing season for planting one and two, respectively. After each respective growing season, total Se concentrations in the broccoli florets and carrots ranged from 6.99 to 7.83 mg kg-1 and 3.15 to 6.25 mg kg-1 in planting one and two, respectively. In broccoli and carrot plant tissues, SeMet (selenomethionine) was the predominant selenoamino acid identified in Se aqueous extracts. In postharvest soils from planting one, phospholipid analyses (PLFA) showed that amending the soil with S. pinnata exerted no effect on the microbial biomass, AMF (arbuscular mycorrhizal fungi), actinomycetes and Gram-positive and bacterial PLFA at both 0-5 and 0-30 cm, respectively, three years later. Successfully producing Se-enriched broccoli and carrots three and four years later after amending soil with Se-enriched S. pinnata clearly demonstrates its potential source as an organic Se enriched fertilizer for Se-deficient regions.